2010
DOI: 10.1111/j.1752-7325.2009.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful fluoride plebiscite in the township of Deniliquin, New South Wales, Australia

Abstract: The council resolved to implement water fluoridation and the residents received fluoridated water in January 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 7 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…10 At the community level, public knowledge of oral diseases has been shown to have a direct impact on the adoption of public health outcomes, such as water fluoridation. 10,11 …”
Section: The Public’s Knowledge and Support Of Water Fluoridationmentioning
confidence: 99%
See 2 more Smart Citations
“…10 At the community level, public knowledge of oral diseases has been shown to have a direct impact on the adoption of public health outcomes, such as water fluoridation. 10,11 …”
Section: The Public’s Knowledge and Support Of Water Fluoridationmentioning
confidence: 99%
“…33 More recently, dentists’ promotion of water fluoridation was successfully carried out as part of a joint campaign effort with the public health department and the media in New South Wales, Australia; in that effort, one prominent local dentist engaged in grassroots efforts to help ensure the successful passage of a municipal water fluoridation plebiscite. 11 Such studies highlight the fact that dentists can and do play important roles during political campaigns by using their good reputations in the community and their ability to organize and lead campaign efforts to educate and persuade the public to vote in favor of water fluoridation. More information is needed to determine the role that dental organizations can and do play in promoting water fluoridation to the public.…”
Section: Dentists’ Effectiveness In Promoting Water Fluoridationmentioning
confidence: 99%
See 1 more Smart Citation
“…The children in the sample from Gosford City in 2012 would have had almost a lifetime exposure to fluoridated water, so the similarity in dmft scores with participants living in the well-established fluoridated area could be expected. Such a finding is of value to councils in other parts of NSW without fluoridation as we have shown that new schemes will bring oral health benefits that are tangible within a short time frame, and counter the views of anti-fluoridationists 16 who argue that water fluoridation is no longer necessary 17 .…”
Section: Discussionmentioning
confidence: 77%
“…The strategies used to engage and mobilize communities included the role of information, communication, community consultation and participation. It is beyond the scope of this article to describe these strategies, but they have been described elsewhere .…”
Section: Introductionmentioning
confidence: 99%